Search for Anomalous $WW\gamma $ and $WWZ$ Couplings with Polarized $e$-Beam at the LHeC - Cakir, I.T.; Cakir, O.; Senol, A.; Tasci, A.T. (Jagiellonian University, 2014)
We examine the potential of the $ep\to\nu_{e}q\gamma X$ and $ep\to\nu_{e}qZX$ processes to search for the anomalous couplings of $WW\gamma$ and $WWZ$ vertices at the LHeC with the electron beam energy of $E_{e}=60$ GeV and $E_{e}=140$ GeV. The difference of maximum and minimum bounds on the anomalous couplings, ($\delta\Delta\kappa_{\gamma}$, $\delta\lambda_{\gamma}$) and ($\delta\Delta\kappa_{Z}$, $\delta\lambda_{Z}$) are obtained as ($0.990$, $0.122$) and ($0.362$, $0.012$) without electron beam polarization at the beam energy of $E_{e}=140$ GeV for an integrated luminosity of $L_{int}=100$ fb$^{-1}$, respectively. With the possibility of $e-$beam polarization, we obtain more improved results as ($0.975$, $0.118$) and ($0.285$, $0.009$) for ($\delta\Delta\kappa_{\gamma}, \delta\lambda_{\gamma}$) and ($\delta\Delta\kappa_{Z}, \delta\lambda_{Z}$), respectively. The results are found to be comparable with the current experimental limits obtained from two-parameter analysis at the lepton and hadron colliders. It is found that the limits on the anomalous couplings ($\Delta\kappa_{Z}$, $\lambda_{Z}$) through the process $ep\to\nu_{e}qZX$ at the LHeC can further improve the current experimental limits.

Comment: 18 pages, 22 figures, 6 tables
Keywords: High Energy Physics - Phenomenology; Nuclear physics; 13. Climate action